Inventory and identification of PARASITOID EGGS and LARVAE of Spodoptera frugiperda (LEPIDOPTERA: NOCTUIDAE) - Maryani Cyccu Tobing,; Augusman Waruwu,; Tuleha Tiurmaida Hutabarat,; Ameilia Zuliyanti Siregar,; Suzanna Fitriany Sitepu, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Spodoptera frugiperda is an invasive pest that invades Indonesia and attacks maize crops. Suppressing the development of pests needs various control methods, including biological control through the application of natural enemies. Therefore, this study was carried out to prepare the inventory and identified the natural enemies, especially parasitoids of S. frugiperda. This study was conducted on farmer's land in Purwobinangun Village, Sei Bingai Sub-District, Langkat District, North Sumatra Province, Indonesia. It was performed using a survey method by taking samples of eggs and larvae of pests S. frugiperda on maize through a purposive sampling (intentional sampling) method. The sampling was carried out on intercropping and monoculture maize crops. The collected eggs and larvae of S. frugiperda were taken to the Agriculture Faculty, Universitas Sumatera Utara plant pest laboratory to be reared until the parasitoids emerged. The result showed that two species of parasitoids were obtained namely Telenomus sp. and Trichogramma sp., with a level of parasitization of egg reached 80% for intercropping and 62.67% for monoculture. The larval parasitoids were obtained from three subfamilies of parasitoids, namely Cheloninae, Microgastrinae, and Campopleginae, with a level of parasitization around 13.2% for monoculture and 9.2% for intercropping.